Controlled superconductivity in infinite-layer Sr0.875La0.125CuO2 films sputter-deposited on BaySr1−yTiO3 buffer layers. (5th January 2016) - Sakuma, Keita; Ito, Masataka; Hajiri, Tetsuya; Ueda, Kenji; Asano, Hidefumi
Abstract: We present a systematic study of the structural and electrical properties of electron-doped infinite-layer Sr0.875 La0.125 CuO2 (SLCO) thin films grown on Ba y Sr1− y TiO3 (BSTO; y = 0.2–0.7) buffer layers. The BSTO ( y = 0.2–0.6) buffer layers were found to allow the coherent growth of SLCO thin films. The coherently tensile-strained SLCO thin films grown on BSTO ( y = 0.6) buffer layers at a low deposition rate of 0.2 nm/min showed a low room-temperature resistivity (118 µΩ cm) and a high T c (36 K). All the other SLCO thin films exhibited a reduced T c of around 20 K. The present results are discussed in terms of correlation among epitaxial strain, c SLCO / a SLCO ratio, and T c .